Analysis of diatomic bond dissociation and formation in terms of the reaction force and the position-dependent reaction force constant - Murray, Jane S.; Toro-Labbe, Alejandro; Clark, Timothy; Politzer, Peter (Journal of Molecular Modeling, 2009)
Bond dissociation and formation in diatomic molecules are analyzed in terms of the reaction force F(R) and the reaction force constant kappa(R). These were determined for a group of 13 molecules from their extended-Rydberg potential energy functions V(R), which are of near-experimental quality. From F(R) and kappa(R) comes a two-stage description of dissociation/formation. In dissociation, the first stage involves stretching of the bond, which is opposed by an increasingly negative retarding force F(R). This reaches a minimum and then begins to weaken in the second stage, which is the transition from stretched molecule to free atoms. Bond formation begins with the reverse transition, driven by a positive F(R) which reaches a maximum for the stretched molecule and then becomes a decreasing restoring force. In the stages in which the system is a stretched molecule, kappa(R) is positive with its maximum at the equilibrium bond length; it is zero at the minimum or maximum of F(R), and negative throughout the transition stages, going through a minimum. kappa(R) < 0 has been found to characterize the transition portion of a reaction. This description of dissociation/formation is reinforced by computed B3LYP and Hartree-Fock force constants at different atom separations for the singlet molecules. Hartree-Fock wave function stability assessments suggest that, for the single-bonded singlet molecules, the onset of electron unpairing in dissociation comes in the neighborhood of the F(R) minimum.
Keywords: Diatomic molecule dissociation/formation; Extended-Rydberg potential energy function; Position-dependent reaction force constant; Reaction force; Wave function stability